Law made simple - Barker, David, 1934- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This 14th edition of Law Made Simple marks the 50th year of the publication for one of the best-selling UK Law books. It is the perfect introduction to the English Legal System, and combines an overview of both the legislation and case law relating to all the foundation subjects, including Contract, Torts, Land, Trusts, Criminal, Public and EU. This book acts as a clear and concise guide for students studying law at any level, and takes into account developments across the curriculum. It is suitable for students studying law at A-Level, or as an excellent background for students thinking of embarking on the study of law or related course at degree level"--
Introduction -- Sources of English law -- The courts today -- Procedure -- The judiciary, law officers and the legal profession -- Human rights and the Law of persons -- The law of contract -- The law of torts -- Trusts -- The law of property -- The law of succession -- Criminal law -- European Union Law.
OCLC-licensed vendor bibliographic record.
Keywords: Law -- England; LAW / General